2020
DOI: 10.1111/jocd.13414
|View full text |Cite
|
Sign up to set email alerts
|

A new technique for the treatment of nasal telangiectasia using atmospheric plasma (voltaic arc dermabrasion): Postoperative pain assessment by thermal infrared imaging

Abstract: Background Nasal telangiectasias are superficial, small vessels in the ala nasi and nasolabial crease with a varying origin. They represent an unaesthetic condition, frustrating patients who frequently request their removal. Microsclerotherapy, electrosurgery, different types of laser therapy, needle‐assisted electrocoagulation, and TRASER therapy have been described for treating this condition. Aims The aim of this study is to describe a novel technique that removes nasal telengectiasias using voltaic arc der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Non-surgical methods are injection of botulinum toxin A, especially for the elevation of the eyebrow tail and glabellar and crow's feet areas [30]. Atmospheric plasma is a new technique used for rejuvenation of the perioral [31] and periocular areas [32,33]. Many studies have described the effectiveness of HA in soft tissue augmentation procedures [34][35][36][37][38], but there are less reports in the literature of eyebrow augmentation with HA [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Non-surgical methods are injection of botulinum toxin A, especially for the elevation of the eyebrow tail and glabellar and crow's feet areas [30]. Atmospheric plasma is a new technique used for rejuvenation of the perioral [31] and periocular areas [32,33]. Many studies have described the effectiveness of HA in soft tissue augmentation procedures [34][35][36][37][38], but there are less reports in the literature of eyebrow augmentation with HA [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study performed by this group showed that the atmospheric plasma technique improves the perioral area [ 13 ] and it was used with success for removing xanthelasma [ 14 ], upper eyelid blepharoplasty [ 15 ], benign skin lesions of the face [ 16 ] and telangiectasia of nose [ 17 ]. The application of atmospheric plasma is well tolerated clinically and allows for an effective improvement of skin laxity and rhytids.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it significantly reduces pain and postoperative edema [ 221 , 222 , 223 , 224 , 225 ]. The use of lasers offers better aesthetic effects compared to other techniques since it does not leave an obvious scar, giving the part of the body where the intervention is performed an excellent restitutio ad integrum [ 221 , 222 , 223 , 224 ]. Photodynamics includes a photochemical and non-thermal biological interaction.…”
Section: Biostimulation and Laser–graft Interactionsmentioning
confidence: 99%